Vertical underwater acoustic channel model in sensor networks for coastal monitoring - Pires, Jorge Andrés (2013)
In this paper a propagation model of acoustic signals in an underwater channel is analyzed. This one is applied to a short vertical communication link. In this way, it's possible to predict the transmission loss, the noise level, the propagation delay and the general shapes of the used acoustic signals. These parameters can be used to design an efficient communication system for transmitting information between a buoy in the surface of the sea, that compose a sensor network for coastal monitoring in the San Jorge gulf, and a data acquisition system in the bottom of the sea. The transmitted signals are encoded using Spread Spectrum Direct Sequence techniques, employing Golay sequences. The simulations results obtained show that it's possible to correctly detect the encoded signals even in those cases where an adverse condition of channel absorption and low SNR are present.